Efforts To Fulfill The Spiritual Needs Of The Elderly In Ngunut Village, Dander District, Bojonegoro - Afandi, Agus Ari; Mulyani, Sri; Rahmawati, Linda (Jurnal EduHealth, 2022)
The decline in the health of the elderly can cause the elderly to be unable to work properly and make the elderly not move either before or change places. This can affect the spiritual behavior of the elderly who were previously able to carry out worship activities and then become a barrier. The purpose of this study was to determine the fulfillment of spiritual needs in the elderly in Ngunut Village, Dander District, Bojonegoro Regency .This research uses a descriptive method. The population is all elderly people aged 60-75 years in Ngunut Village, Dander District as many as 483 . Sampling used purposive sampling so that the number of samples obtained was 50 respondents. Collecting data using a questionnaire, then editing, coding, scoring and tabulating then presented in the form of tables and frequencies with percentages and narration. The results showed that of the 50 respondents studied, more than half of the respondents, namely as many as 31 people (62.0%) made efforts to fulfill enough spiritual needs. To increase unfulfil spiritual needs by prioritizing spirituality and increasing the intensity of spiritual needs.